1991
DOI: 10.1111/j.1365-2672.1991.tb04589.x
|View full text |Cite
|
Sign up to set email alerts
|

Surface characteristics and adhesion of Escherichia coli and Staphylococcus epidermidis

Abstract: Surface hydrophobicity, surface electrokinetic potential and the ability to adhere to nitric-acid cleansed glass surfaces has been assessed throughout the growth, in batch culture, of Escherichia cola and Staphylococcus epidermidis. In both instances adhesiveness and surface hydrophobicity decreased in early-to mid-exponential phase. Cell surface charge, on the other hand became more electro-negative for E . coli but electro-neutral for Staph. epidermidis as the cells proceeded to divide. Adhesiveness correlat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
44
0
1

Year Published

1996
1996
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(52 citation statements)
references
References 25 publications
7
44
0
1
Order By: Relevance
“…Similar to our results, another study reported that significantly fewer S. aureus adhered to polypropylene than to polyester sutures [6]. This could be related to the interplay of adhesion, hydrophobicity, surface growth, electrostatic forces, and application of friction of the infecting organisms, as reported in the literature [5,9,23]. The adhesion of coagulase negative staphylococcus and E. coli is faster on positively charged copolymers than on negatively charged copolymers because of the negative charge on bacteria [24].…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Similar to our results, another study reported that significantly fewer S. aureus adhered to polypropylene than to polyester sutures [6]. This could be related to the interplay of adhesion, hydrophobicity, surface growth, electrostatic forces, and application of friction of the infecting organisms, as reported in the literature [5,9,23]. The adhesion of coagulase negative staphylococcus and E. coli is faster on positively charged copolymers than on negatively charged copolymers because of the negative charge on bacteria [24].…”
Section: Discussionsupporting
confidence: 79%
“…The percentage of attached E. coli has been reported to decrease as the surface free energy of the polymer increases [2]. In another study, adhesiveness correlated directly with the surface electronegativity of Staphylococcus epidermidis, but inversely for E. coli [23]. Graft 10 included polyglactin, and minimal E. coli adhesion was observed on polyglactin prostheses used in urology [25].…”
Section: Discussionmentioning
confidence: 99%
“…Earlier, Gilbert et al (1991) also found that the growth phase of E. coli and S. epidermidis affected the electrophoretic mobility of these bacteria. E. coli was shown to be less negatively charged in its lag phase than in its early exponential growth phase (Allison et al, 1990b), S. epidermidis showed a decrease in negative surface charge towards neutrality with progression of the growth phase into mid-exponential phase and restoration of the negative charge after entry into the stationary phase.…”
Section: Discussionmentioning
confidence: 99%
“…Physico-chemical studies on microbial adhesion to surfaces are typically carried out with organisms suspended in buffers to avoid microbial growth or other associated complications (Van Loosdrecht et al, 1990). In vitro studies have identified changes in antimicrobial efficacy (Evans et al, 1990(Evans et al, , 1991 …”
Section: Introductionmentioning
confidence: 99%
“…[12,13] Previous studies have shown a correlation between surface hydrophobicity and in vitro adherence to epithelial cells. [14][15][16] We observed that any change in the surface hydrophobicity of bacteria resulted in a corresponding change in bacterial adherence to epithelial cells. Oxidative stress also caused a decrease in haemolysin synthesis in both the strains of E. coli.…”
Section: Discussionmentioning
confidence: 99%